2017
DOI: 10.1097/sla.0000000000001988
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte Ratio is a Predictive Marker for Invasive Malignancy in Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: NLR is an independent predictive marker for the presence of IPMN-associated invasive carcinoma. Further prospective studies are needed to assess the predictive ability of NLR and how it can be applied in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 48 publications
6
93
0
Order By: Relevance
“…Absolute peripheral blood neutrophil count more than 8.0 × 10 9 /L was considered as neutrophilia, and absolute peripheral blood lymphocyte count was less than 1.0 × 10 9 /L as lymphocytopenia. In addition, the number of platelets in the blood more than 400 × 10 9 /L was considered as thrombocytosis …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute peripheral blood neutrophil count more than 8.0 × 10 9 /L was considered as neutrophilia, and absolute peripheral blood lymphocyte count was less than 1.0 × 10 9 /L as lymphocytopenia. In addition, the number of platelets in the blood more than 400 × 10 9 /L was considered as thrombocytosis …”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) are routinely used and convenient inflammatory markers that reflect this immune response, and have been demonstrated to be prognostic for several malignancies including pancreatic Carcinoma . Recently, both markers have also been shown associated with prognosis in pancreatic cystic neoplasms (PCNs) . However, the association between systemic inflammatory markers and biological behavior of SPTP has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators from our Institution have reported an association between tumorassociated neutrophils (TANs) and advanced IPMN lesions (78). The recent publication of Gemenetzis et al (79) evaluating the correlation between NLR and platelet-tolymphocyte ratio (PLR) values and the presence of invasive carcinoma in patients with IPMN. Despite the limitations of the study that the authors acknowledge, including its retrospective nature and the non-specificity of the results since blood is a complex fluid with high cellular turnover, the striking finding was that NLR was significantly elevated in patients with IPMN-associated invasive carcinoma in a value higher than 4 (79).…”
Section: Peripheral Blood Cellmentioning
confidence: 99%
“…More recently, the neutrophil-to-lymphocyte ratio (NLR) in blood has been evaluated as a novel predictor of HGD and invasive carcinoma, which could presumably reflect the systemic immune response elicited by cancer, among other potential physiologic mechanisms [38,39]. In a series of 272 patients with resected IPMN from the Johns Hopkins Hospital, Gemenetzis et al [39] found that an NLR > 4 was significantly associated with invasive carcinoma, independent of MPD size, presence of mural nodules, jaundice, and cyst size.…”
Section: Circulating Biomarkers For Prediction Of High-risk Intraductmentioning
confidence: 99%
“…In a series of 272 patients with resected IPMN from the Johns Hopkins Hospital, Gemenetzis et al [39] found that an NLR > 4 was significantly associated with invasive carcinoma, independent of MPD size, presence of mural nodules, jaundice, and cyst size. Notably, a higher NLR was not associated with HGD without invasive carcinoma.…”
Section: Circulating Biomarkers For Prediction Of High-risk Intraductmentioning
confidence: 99%